2018
DOI: 10.3389/fncel.2018.00492
|View full text |Cite
|
Sign up to set email alerts
|

Biological Sex, Estradiol and Striatal Medium Spiny Neuron Physiology: A Mini-Review

Abstract: The caudate-putamen, nucleus accumbens core and shell are important striatal brain regions for premotor, limbic, habit formation, reward, and other critical cognitive functions. Striatal-relevant behaviors such as anxiety, motor coordination, locomotion, and sensitivity to reward, all change with fluctuations of the menstrual cycle in humans and the estrous cycle in rodents. These fluctuations implicate sex steroid hormones, such as 17β-estradiol, as potent neuromodulatory signals for striatal neuron activity.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
29
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 34 publications
(32 citation statements)
references
References 88 publications
3
29
0
Order By: Relevance
“…There are major differences in the reproductive cycle of women and female rodents: the duration of the cycle, the cycle pattern of estradiol and progesterone, and the amplitude of hormone level variations. However, when the hormonal ratio over the phases is compared, some analogies are conventionally made: the follicular phase is comparable to the estrus phase (progesterone < estradiol) and the luteal phase to the nonestrus phase (progesterone > estradiol) 200,202 .…”
Section: Figure Legendsmentioning
confidence: 99%
See 1 more Smart Citation
“…There are major differences in the reproductive cycle of women and female rodents: the duration of the cycle, the cycle pattern of estradiol and progesterone, and the amplitude of hormone level variations. However, when the hormonal ratio over the phases is compared, some analogies are conventionally made: the follicular phase is comparable to the estrus phase (progesterone < estradiol) and the luteal phase to the nonestrus phase (progesterone > estradiol) 200,202 .…”
Section: Figure Legendsmentioning
confidence: 99%
“…A proposed brain mechanism model of the role of estradiol and progesterone in cocaine relapse in rodent models . There is evidence that estradiol potentiates striatal and nucleus accumbens (NAc) dopamine release by modulating GABAergic neurotransmission of medium spiny neurons (MSN) through collaterals synapsing on dopamine neurons 202,203 . This effect is likely mediated by membrane estrogen receptors (membrane-associated ERα and membrane-associated ERβ) expressed in MSNs 204 .…”
Section: Figure Legendsmentioning
confidence: 99%
“…The different neuroprotective action of estradiol in male and female animals may be also partially determined by the sex dimorphic structural and functional organization of specific neuronal circuits (Gillies and McArthur, 2010b) and by sex differences in neuronal function and plasticity in response to the hormone (Hyer et al, 2018;Krentzel and Meitzen, 2018). In these sex differences also participate the associated glial cells.…”
Section: Subcellular and Cellular Contributions To Sex Differences Inmentioning
confidence: 99%
“…Estradiol can both permanently organize and temporarily modulate neurons and behavior (McCarthy & Arnold, 2011; Woolley, 2007). Estradiol can be produced not only by the gonads, but by neural tissue itself via expression of the enzyme aromatase (Balthazart, Choleris, & Remage‐Healey, 2018; Krentzel & Meitzen, 2018). The presence of aromatase in a brain region suggests dynamic control of estrogen production, which can directly impact estrogen‐sensitive neurons in a temporally rapid manner.…”
Section: Introductionmentioning
confidence: 99%
“…No previous study has identified nuclear ER expression in the striatum. Sex‐specific estradiol action has been shown to modulate numerous aspects of striatal neuron phenotype (Cao, Willett, Dorris, & Meitzen, 2018; Meitzen, Meisel, & Mermelstein, 2018; Peterson, Mermelstein, & Meisel, 2015; Staffend, Loftus, & Meisel, 2011; Tozzi et al, 2015), neuromodulator signaling such as dopamine (Calipari et al, 2017; Di Paolo, 1994; Walker, Ray, & Kuhn, 2006; Yoest, Cummings, & Becker, 2014, 2018), striatal‐influenced cognitive, social, emotional and premotor behaviors, as well as the relevant neuropsychiatric (Lorsch et al, 2018), motor (Krentzel & Meitzen, 2018), and addiction disorders (Beltz, Beery, & Becker, 2019). This rich body of data has been dominated by models and discussions of the role of membrane ER.…”
Section: Introductionmentioning
confidence: 99%